(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
Trade organizations are one of the fundamental economic entities in the Russian economy after mining companies, which is due to the low development of the manufacturing sector in the country’s economy. In this article, a brief assessment of the state of trade in Russia is carried out, the dynamics of the number of trade organizations in the country, the dynamics of trade turnover are considered, conclusions are drawn about the level of profitability of trade organizations over the ten-year period under study.